Engineering contracts - Ribeiro, R. A. (Robert A.) (Butterworth-Heinemann, 1996)
Engineering Contracts is intended for those who wish to acquire skills in drafting, negotiating and working with commercial and engineering contracts. It aims to bring a different approach to the subject; combining the traditional legal perspective of the law of contract with the needs of the commercial manager or engineer who is seeking solutions to technical and commercial problems. The context within which these matters are examined is as wide as possible; for the purposes of illustration cases are drawn from the fields of mechanical, electrical, chemical, electronic and civil engineering, as well as from construction and building contracts. In many cases the important points are common to all disciplines, for instance the importance of ensuring that what has been specified is what is delivered by a supplier, and that any such delivery or indeed any event critical to the timely conclusion of a project takes place when arranged. There is advice on how to the concepts broached relate to real-life requirements and the reader will benefit from the helpful 'Legal Questions Answered' section that is included in most chapters. In addition there is a summary guide to drafting an engineering contract, a section on the relevant statutes and other legislation in force, and a list of the engineering institutions and their standard forms of contract. Case-studies of genuine and practical origin from the author's wide-ranging experience in industrial practice complete this comprehensive treatment of the subject matter.